Analysis of the Management of Incoming Letters at the South Sulawesi Provincial Health Office - Yusra Yusra; Muh. Nasrullah; Muh. Darwis (International Journal of Administration and Education (IJAE), 2024)
This study aims to find out the analysis of the management of incoming mail at the South Sulawesi Provincial Health Office. This research is qualitative, using data collection techniques through observation, interviews and documentation. The research informants were 3 employees of the South Sulawesi Provincial Health Office. The results of this study show that the management of incoming letters at the South Sulawesi Provincial Health Office is running "well". Judging from the aspect of receiving letters, namely receiving letters is done manually by paying attention to the purpose of the sender, sorting to distinguish between personal and official letters, checking that the letters are correct and not damaged, and ensuring that the letters are well received by the relevant fields. The aspect of directing incoming letters, namely directing incoming letters, is carried out by including a disposition sheet that records the instructions of the leadership After being received in the administration section, the letter is put into the agenda book and sent to the head of the agency. Original mail can be sent or distributed. In the case of recording incoming mail, incoming mail is recorded in a notebook and the officer uses an agenda stamp as proof that the letter has been recorded. The storage aspect includes storing incoming mail manually, i.e. it is physically stored in the mail. To do this, a folder is used to store the letter in the refrigerator. From the aspect of submission, the incoming letter is submitted to the relevant parties based on the disposition of the leadership by including two introductory sheets that must be paraphrased as a receipt.